The weight of islands: Leveraging Grenada's material stocks to adapt to climate change. (11th April 2019) - Symmes, Rob; Fishman, Tomer; Telesford, John N.; Singh, Simron J.; Tan, Su‐Yin; De Kroon, Kristen
Abstract: The building stock consumes large amounts of resources for maintenance and expansion which is only exacerbated by disaster events where large‐scale reconstruction must occur quickly. Recent research has shown the potential for application of material stock (MS) accounts for informing disaster risk planning. In this research, we present a methodological approach to analyze the vulnerability of the material stock in buildings to extreme weather events and sea‐level rise (SLR) due to climate change. The main island of Grenada, a Small Island Developing State (SIDS) in the Caribbean region, was used as a case study. A bottom‐up approach based on a geographic information system (GIS) is used to calculate the total MS of aggregate, timber, concrete, and steel in buildings. The total MS in buildings in 2014 was calculated to be 11.9 million tonnes (Mt), which is equivalent to 112 tonnes per capita. Material gross addition to stock (GAS) between 1993 to 2009 was 6.8 Mt and the average value over the time period was 4.0 tonnes per capita per year. In the year following Hurricane Ivan (2004), the per capita GAS for timber increased by 172%, while for other metals, GAS spiked by 103% (compared to average growth rates of 11% and 8%, respectively, between 1993 and 2009). We also ran a future "Ivan‐II" scenario and estimated a hypothetical loss of between 135 and 216 kilotonnes (kt) of timber from the building stock. The potential impact of SLR is also assessed, with an estimated 1.6 Mt of building material stock exposed under a 2‐m scenario. We argue that spatial material stock accounts have an important application in planning for resilience and provide indication of the link between natural disaster recovery and resource use patterns.